Impact Of Competence, Job Design, Job Satisfaction on Employee Directorate General of Taxes Performance - Nurcahyono Nurcahyono; R Ery Wibowo; Ida Kristiana (UIN Raden Mas Said Surakarta, 2020)
This research aims to prove empirically the factors that affect the performance of employees at the Directorate General of Taxes (DJP) East Java which are divided into three DGT, namely East Java I, II and III and spread over three Middle Tax Service Offices, forty Primary Tax Service Offices. The unit of analysis in this research is an employee in charge of the account representative, billing, inspection, data and information processing, tax bailiff and the general section. The sampling method used was cluster sampling, this was chosen because the research area was spread wide. Analysis of research data using SEM-PLS with the help of the WarpPLS 7.0 application. The results showed that the factors that can improve performance, namely competence, compensation, and job design (job rotation and job expansion) and job satisfaction are supporting factors used by companies to improve employee performance, but in this study job satisfaction can only be mediated. partial because it has a VAF value <80%, indicating that job satisfaction is not enough to increase high performance